Plasma processing and quantitative characterization of 3D polymeric materials to enhance antibacterial properties for biomedical applications - Mann, Michelle N., author; Fisher, Ellen R., advisor; Kota, Arun, committee member; Reynolds, Melissa, committee member; McCullagh, Martin, committee member (Colorado State University. Libraries, 2018)
To view the abstract, please see the full text of the document.
Keywords: anti-fouling; PECVD; plasma surface modification; biofilm formation; antibacterial; plasma processing